PROMOVAREA DREPTURILOR FEMEII ÎN MOLDOVA - Borșevski, Andrei, Sosna Alexandru (SUPREMANCE OF LAW, 2018)
The equality of women and men is one of the conditions for ensuring social justice, as well as the necessary and basic prerequisite for achieving equality, development and peace. This article became possible thanks to the support of the EU Delegation to Moldova in the framework of the Confidence-building Measures Programme, as well as the Government of Sweden and UN-Women in the framework of the Cooperation Agreement for the implementation of the project with UN-Women (United Nations Entity for Gender Equality and the Empowerment of Women). The views and opinions expressed here are those of the authors and do not necessarily reflect the views of the EU Delegation to Moldova, UN Women, United Nations, Government of Sweden.
Keywords: Equal rights; leadership training; women; participation in public life.